Pollution Maintenance Techniques in Coastal High Voltage Installations - Siderakis, K.; Pylarinos, D.; Thalassinakis, E.; Vitellas, I.; Pyrgioti, E. (Engineering, Technology & Applied Science Research, 2011)
Pollution of outdoor high voltage insulators is a common problem for utilities, with a considerable impact to power system reliability. In an effort to prevent possible flashovers due to pollution, many methods have been applied, aiming to improve the insulation performance, either by suppressing the formation of surface conductivity or by increasing the possible insulation level. In the case of substations, the selection of the appropriate technique is complex due to certain issues correlated to the nature of the installation. In this paper, several techniques usually implemented by utilities, are investigated based on the experienced gained in the case of Crete, a Greek island in southern Europe, where due to the coastal development of the power system, the majority of high voltage installations are exposed to intense marine pollution. The technique of coating insulators with Room Temperature Vulcanized Silicone Rubber (RTV SIR) has proved rather efficient and therefore is presented extendedly. Correlation of the material behaviour with environmental conditions is discussed and results from long term monitoring, including environmental parameters and leakage current measurements, in a 150 kV Substation are presented. It is shown that RTV SIR coatings have remarkably suppressed surface activity and that porcelain insulators exhibit different activity period when coated.